DEVELOPMENT OF FLAT-BASED LEARNING MEDIA MINIATURE OF THE HOUSE IN MATHEMATICS AT SD SUKASARI 4 - Magdalena, Ina; Nuraini, Nuraini; Setiawan, Thoni Putra (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This study aimed to determine the development of miniature house-based learning media for elementary school mathematics, to determine the quality of miniature house media, to determine the effectiveness of the media when applied to learning in 1st grade students of SD Sukasari 4 and to determine the increase in achievement after using miniature house media. In this study, as many as 31 first-year students from SD Sukasari 4 participated, namely 14 from a control class and 17 from an experimental class. This research uses qualitative data gathered through in-depth interviews, as well as quantitative data gleaned from surveys and other similar instruments. T and N-gain tests are used for analysis. The study's findings indicate that this form of educational media has gone through a number of iterations, including the identification of opportunities and challenges, the collection of data, the development of a prototype, the validation of that prototype, the conduct of user tests, the revision of that prototype, and finally the production of mass quantities of the product. The produced medium is fit for purpose, as evidenced by the acquired findings of the assessment from the material expert, who gave it a score of 143 on good criteria. This miniature house-based flat building learning media is effectively used in Grade I students in Mathematics learning based on the results of the t test can be seen the t-statistic value of 6,905 > t table 2,035. Besides, the N-gain analysis showed that in the control class of 0,27 with the criteria low, while in the experimental class it was 0,70 with high criteria. Hence, the increase in achievement is in the high category.